2015
DOI: 10.1038/ncomms8079
|View full text |Cite|
|
Sign up to set email alerts
|

FoxO1 integrates direct and indirect effects of insulin on hepatic glucose production and glucose utilization

Abstract: FoxO proteins are major targets of insulin action. To better define the role of FoxO1 in mediating insulin effects in the liver, we generated liver-specific insulin receptor knockout (LIRKO) and IR/FoxO1 double knockout (LIRFKO) mice. Here we show that LIRKO mice are severely insulin resistant based on glucose, insulin and C-peptide levels, and glucose and insulin tolerance tests, and genetic deletion of hepatic FoxO1 reverses these effects. 13C-glucose and insulin clamp studies indicate that regulation of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
149
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(168 citation statements)
references
References 33 publications
14
149
2
3
Order By: Relevance
“…20,21 Previous studies demonstrated that FoxO1 activation dysregulated mitochondrial function as well as glucose and lipid metabolism in the liver; thus, ablation of FoxO1 in the liver reverses the adverse changes of mitochondria and metabolism. [38][39][40][41][42] We and others found that FoxO1 also regulated adipogenesis, 3,43,44 a process which may promote adipose expansion via hyperplasia. 6,29,45 Moreover, aberrant adiposity may result from adipocyte or LD hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Previous studies demonstrated that FoxO1 activation dysregulated mitochondrial function as well as glucose and lipid metabolism in the liver; thus, ablation of FoxO1 in the liver reverses the adverse changes of mitochondria and metabolism. [38][39][40][41][42] We and others found that FoxO1 also regulated adipogenesis, 3,43,44 a process which may promote adipose expansion via hyperplasia. 6,29,45 Moreover, aberrant adiposity may result from adipocyte or LD hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocytes, the forkhead transcription factors of the FoxO subfamily FoxO1, FoxO3, and FoxO4 (FoxOs) mediate a substantial portion of insulin-regulated gene transcription (1)(2)(3)(4)(5). During fasting, FoxOs are active, whereas insulin signaling suppresses FoxO activity via Akt-mediated phosphorylation and nuclear exclusion (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Эти три белка наряду с большим количеством общих транскрипционных мишеней обладают специфическими транскрипционными мишенями, определяющими их уникальные функции. Так, FOXO1 играет ключевую роль в регуляции чувствительности к инсулину [17][18][19] (рис. 2).…”
Section: сахарный диабет Diabetes Mellitusunclassified
“…Так, селективный нокаут в печени инсулино-вого рецептора [17] или киназ Akt 1 и Akt 2 [26] приво-дил к развитию гипергликемии и нарушению регуляции глюконеогенеза. Множественный нокаут в печени у этих животных по гену инсулинового рецептора или Akt 1 и Akt 2, а также по гену FOXO1 приводил к проявле-нию нормального фенотипа (животные были способны поддерживать нормальный уровень глюкозы в крови).…”
Section: сахарный диабет Diabetes Mellitusunclassified
See 1 more Smart Citation